Expression of TLE3 by bone marrow stromal cells is regulated by canonical Wnt signaling. Issue 4 (17th January 2014) - Kokabu, Shoichiro; Sato, Tsuyoshi; Ohte, Satoshi; Enoki, Yuichiro; Okubo, Masahiko; Hayashi, Naoki; Nojima, Junya; Tsukamoto, Sho; Fukushima, Yosuke; Sakata, Yasuaki; Katagiri, Takenobu; Rosen, Vicki; et al.
Abstract : Transducing‐like enhancer of split 3 (TLE3), one of the Groucho/TLE family members, targets Runx2 transcription and suppresses osteoblast differentiation in bone marrow stromal cells (BMSCs). Here, we identify Wnt responsive elements of the TLE3 promoter region through comparative genomic and functional analyses and show that expression of TLE3 is increased by Wnt signaling, which is important for osteoblast differentiation. We also demonstrated that TLE3 is able to suppress canonical Wnt signaling in BMSCs. Taken together, our data suggest that induction of TLE3 by Wnt signaling is part of a negative feedback loop active during osteoblast differentiation. Abstract : ECR between M. musculus and H. sapiense, contains putative TCF/LEFs binding elements. Wnt/β‐catenin signaling regulates TLE3 expression in bone marrow stromal cells. TLE3 suppresses Wnt/β‐catenin signaling in bone marrow stromal cells.